2021
DOI: 10.3389/fnbeh.2021.615798
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Oxycodone Exposure Affects Early Life Communicative Behaviors, Sensorimotor Reflexes, and Weight Trajectory in Mice

Abstract: Nationwide, opioid misuse among pregnant women has risen four-fold from 1999 to 2014, with commensurate increase in neonates hospitalized for neonatal abstinence syndrome (NAS). NAS occurs when a fetus exposed to opioids in utero goes into rapid withdrawal after birth. NAS treatment via continued post-natal opioid exposure has been suggested to worsen neurodevelopmental outcomes. We developed a novel model to characterize the impact of in utero and prolonged post-natal oxycodone (Oxy) exposure on early behavio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Several animal models for NOWS have been developed ( Fodor et al, 2014 ; Chen et al, 2015 ; Byrnes and Vassoler, 2018 ), differing in time of exposure (i.e., prenatally, postnatally, or both), specific opioid (morphine, heroin, methadone, oxycodone, and/or buprenorphine), and dosing regimen (e.g., injections, pellets, mini-pumps; Byrnes and Vassoler, 2018 ; Robinson et al, 2020 ; Minakova et al, 2021 ). The physiological and behavioral consequences of opioids on development depends on the timing, duration, and route of drug administration ( Fodor et al, 2014 ; Byrnes and Vassoler, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several animal models for NOWS have been developed ( Fodor et al, 2014 ; Chen et al, 2015 ; Byrnes and Vassoler, 2018 ), differing in time of exposure (i.e., prenatally, postnatally, or both), specific opioid (morphine, heroin, methadone, oxycodone, and/or buprenorphine), and dosing regimen (e.g., injections, pellets, mini-pumps; Byrnes and Vassoler, 2018 ; Robinson et al, 2020 ; Minakova et al, 2021 ). The physiological and behavioral consequences of opioids on development depends on the timing, duration, and route of drug administration ( Fodor et al, 2014 ; Byrnes and Vassoler, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, significant clusters of diverse microstructural differences were frequently identified in the somatosensory cortex, motor cortex, dorsal striatum, and their respective adjacent white matter. We and others have described delayed development of several sensorimotor-based developmental milestones including the cliff aversion, surface righting, and forelimb grasp task, among others, which suggest opioid exposed offspring may lack the ability to translate multimodal sensory input into complex motor behaviors 21,[63][64][65] . Furthermore, we have also demonstrated that PME disrupts synaptic signaling in the somatosensory cortex, motor cortex and dorsal striatum using brain slice, patch-clamp electrophysiology 21,26,27 .…”
Section: Discussionmentioning
confidence: 88%
“…Novel methods to accurately trace the influence of germline modifications through embryogenesis and development will be crucial for advancing the field and developing effective Epidemiological evidence suggests that parental opioid exposure is associated with lower birth weight and adverse developmental outcomes in offsprings (Hunt et al, 2008). Preclinical research found that maternal exposure to opioids from conception through the pup weaning process results in reduced body weight in the offsprings (Minakova et al, 2021). By contrast, other research has indicated that maternal exposure to oxycodone did not affect the birth weight or body weight on postnatal day 8, day 21, and day 30 (Minakova et al, 2022).…”
Section: Discussionmentioning
confidence: 99%